Sustainable urban planning patterns and techniques in historical contextsCase study (Bolaghi neighborhood of Qazvin) - Amir Alimmohamadi; Hassan Sattari Sarebangholi; Mahsa Faramarzi Asl; Mohammadreza Pakdel (تحقیقات کاربردی علوم جغرافیایی)
Abstract Historical contexts have rich cultural and cultural resources and are not very important not only because of the existence of valuable historical buildings and spaces, but also because they are real narratives of the life and activities of human beings who have lived throughout life. They lived in them themselves. Today, due to urban development and the blockade of the technology of historical textures, the issue of restoration of cultural and historical textures and the implementation of urban design projects in them has faced a double challenge of the intervention and protectionist approach. According to these two approaches, new constructions and contemporary architecture do not have enough identity to be included in the valuable urban contexts, and the process of burnout has been manifested more rapidly in historical contexts. The need to pay attention to the reconstruction and protection of historical contexts with a comprehensive approach and taking into account the physical, legal, environmental, economic and social dimensions is one of the objectives of the present study. This research has been studied in terms of practical purpose and with a qualitative approach and using content analysis method and to collect the required information and data, documentary studies and field studies have been used. The findings show that the neighborhood is worn out and to recreate the historical core of Qazvin city, the approach of urban revitalization and urban and strategic regeneration strategies is essential in line with the principles of sustainable development.